2012
DOI: 10.1007/s00011-012-0562-3
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen and nitrogen species in sepsis-induced hepatic microvascular dysfunction

Abstract: Objective and designHepatic microvascular dysfunction is a critical event in the development of liver failure during sepsis. Activated blood cells and reactive oxygen and nitrogen species (RONS) have been implicated in the pathogenesis of sepsis.MethodsIntravital-videomicroscopy was used to determine whether RONS contribute to the recruitment of leukocytes/platelets in the hepatic microvasculature during sepsis. Six hours following cecal-ligation and puncture (CLP), disturbances of the hepatic microvasculature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…In mice with cecal ligation and puncture (CLP)-induced sepsis and in eNOS KO mice, increased leukocyte and platelet adhesion was detected. In this study, eNOS KO mice or mice treated with L-NAME had an increase in blood cell recruitment in the hepatic microvasculature following CLP 141 . Treatment with pravastatin, a member of the statin class of drugs used to lower high cholesterol and triglycerides, resulted in increased eNOS function and expression in LPS-injected rats, leading to improvement of eNOS-mediated vessel relaxation 23 .…”
Section: Role Of Enos In the Microcirculation During Sepsis—integratimentioning
confidence: 62%
“…In mice with cecal ligation and puncture (CLP)-induced sepsis and in eNOS KO mice, increased leukocyte and platelet adhesion was detected. In this study, eNOS KO mice or mice treated with L-NAME had an increase in blood cell recruitment in the hepatic microvasculature following CLP 141 . Treatment with pravastatin, a member of the statin class of drugs used to lower high cholesterol and triglycerides, resulted in increased eNOS function and expression in LPS-injected rats, leading to improvement of eNOS-mediated vessel relaxation 23 .…”
Section: Role Of Enos In the Microcirculation During Sepsis—integratimentioning
confidence: 62%
“…Moreover, the isoforms of constitutive NOSs are considered to be parts of two signaling pathways in the cell (Malakhov et al, 2009 ). There are many publications that reveal the involvement of iNOS in physiological synthesis of NO and impact of eNOS and nNOS on extra synthesis of NO in infection, allergic, and autoimmune diseases (Wahl et al, 2003 ; Jarazo-Dietrich et al, 2012 ; Singer et al, 2013 ). Activation of iNOS is a component of many protective-adaptive reactions (Das and Das, 2008 ; Ye et al, 2010 ; Abu-Amara et al, 2012 ).…”
mentioning
confidence: 99%
“…[ 9 ] In an animal study, ROS and reactive nitrogen species were reported to cause hepatic microvascular dysfunction during sepsis. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Lower ALT concentration can occur in the setting of vitamin B6 deficiency. [ 10 ] Vitamin B6 is an antioxidant and is a strong quencher of ROS. In the ESBL group, vitamin B6 may be consumed largely due to high ROS, resulting in decreased ALT levels.…”
Section: Discussionmentioning
confidence: 99%